GROWTH, DEVELOPMENT AND EGG EFFICIENCY OF THE PARENTAL FORM OF THE DOMINANT D-149 CROSS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study investigates the growth dynamics, developmental characteristics, and egg efficiency of the parental form of the Dominant D-149 cross, a highly productive egg-laying line originally bred in the Czech Republic and successfully adapted to the climatic conditions of Uzbekistan. Experimental observations were conducted on the Research Institute’s experimental farm under standardized management conditions. The study evaluates live weight progression, egg-laying performance, and feed conversion ratio to determine economic efficiency and adaptability. Results show that the parental stock exhibits stable growth patterns, early maturity, and high egg-laying persistence with over 92% peak productivity. These findings highlight the genetic and environmental interactions that determine poultry performance in Uzbekistan’s agro-industrial systems.